Harvest Control Rules of Multispecies Scads (Decapterus spp.) Fishery in Blitar Waters, East Java - Ledhyane Ika Harlyan; Shobriyyah Afifah Nabilah; Daduk Setyohadi; Muhammad Arif Rahman; Supapong Pattarapongpan (Faculty of Fisheries and Marine Universitas Airlangga, 2022)
Highlight ResearchThe feedback harvest control rule resulted in the lowest allowable biological catch estimation than the surplus production models. The feedback harvest control rule adapted the recent years of historical catch data.The surplus production models might result in over or under catch estimation, not considering the recent data.This multispecies fishery could not provide species specific data as surplus production models required; therefore, it might be better to use the feedback harvest control rule that has been validated for multispecies fisheries. AbstractScads fishery in Blitar waters is a multispecies fishery applying harvest control rules (HCRs) from conventional single-species approaches which technically, may not be applicable to employ in such mixed-species data composed from the multispecies fishery. The feedback HCR is an alternative validated harvest control rule that can be applied for a multispecies fishery. The aim of this study was to technically compare the application of the feedback HCR and conventional single species approaches in terms of estimating the future allowable biological catch (ABC). Therefore, in this study, ABC was estimated by applying three HCRs, the feedback HCR, and two conventional HCRs which was based on single-species approaches applying surplus production models, Schaefer Model and Fox model into catch and effort of scads fisheries data series of 2011 – 2020. The results showed that the ABC estimation of the feedback HCR was a half lower than that of both conventional models. It was biologically safer to apply the feedback HCR to set the annual total allowable catch (TAC) than the other two HCRs. The feedback HCR presented an initial step toward sustainably managing multispecies fisheries while dealing with data-limited conditions.